Molecular complexity of mammary glands development: a review of lactogenic differentiation in epithelial cells - Jena, Manoj Kumar; Khan, Farheen Badrealam; Ali, Syed Azmal; Abdullah, Abdullah; Sharma, Amarish Kumar; Yadav, Vikas; Kancharla, Sudhakar; Kolli, Prachetha; Mandadapu, Gowtham; Sahoo, Anjan Kumar; Rath, Prasana Kumar; Taneera, Jalal; et al. (Taylor and Francis, 2023)
The mammary gland is a dynamic organ with various physiological processes like cellular proliferation, differentiation, and apoptosis during the pregnancy-lactation-involution cycle. It is essential to understand the molecular changes during the lactogenic differentiation of mammary epithelial cells (MECs, the milk-synthesizing cells). The MECs are organized as luminal milk-secreting cells and basal myoepithelial cells (responsible for milk ejection by contraction) that form the alveoli. The branching morphogenesis and lactogenic differentiation of the MECs prepare the gland for lactation. This process is governed by many molecular mediators including hormones, growth factors, cytokines, miRNAs, regulatory proteins, etc. Interestingly, various signalling pathways guide lactation and understanding these molecular transitions from pregnancy to lactation will help researchers design further research. Manipulation of genes responsible for milk synthesis and secretion will promote augmentation of milk yield in dairy animals. Identifying protein signatures of lactation will help develop strategies for persistent lactation and shortening the dry period in farm animals. The present review article discusses in details the physiological and molecular changes occurring during lactogenic differentiation of MECs and the associated hormones, regulatory proteins, miRNAs, and signalling pathways. An in-depth knowledge of the molecular events will aid in developing engineered cellular models for studies related to mammary gland diseases of humans and animals.